Hemangioma treated with sclerosing solution (sodium tetradecyl-sotradecol) - Gervasio, Natividad C. (The Journal of the Philippine Dental Association)
Management of hemangiomas is multivactorial in nature. Age of patient, location, and size of the lesions are of primary considerations. The decision as to the choice of treatment modalities ranges from non-surgical to surgical.